Pengembangan Video Pembelajaran Berbasis Artificial Intelligence Berbantuan Lumen5 Pada Materi Hidrokarbon Di SMA/MA : Penelitian - Zuhripa Oktavia Ranni; Harizon; Febbry Romundza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the development process, feasibility, teacher assessment, and student responses to artificial intelligence (AI)-based learning videos using the Lumen5 platform on Hydrocarbon material in SMA/MA. The development model used is Lee & Owens (2004), which consists of five stages: analysis, design, development, implementation, and evaluation. This study was conducted through a small group trial involving 10 students at SMAN Titian Teras H. Abdurrahman Sayoeti. The data analysis technique used was a combination of qualitative and quantitative methods. The results of the study showed that the developed learning videos were declared feasible and valid. The validation results by material experts obtained an average score of 3.8, while validation by media experts obtained an average of 4.44. The teacher's assessment of this media was also very good with an average score of 4.6. Meanwhile, the results of the trial in small groups showed a total score of 551 with a percentage of 91.83%, which was categorized as